Age estimation by assessment of dentin translucency in permanent teeth - Jigna S Shah; Ashish F Ranghani; Piyush G Limdiwala (Wolters Kluwer Medknow Publications, 2020)
Aim: To estimate the age by evaluating the length of dentin translucency in ground sections of extracted teeth using digital scanner and tools of GIMP 2.8 software for dental age estimation. Materials and Methods: Fifty extracted single-rooted permanent teeth from 50 different individuals and their 0.25-mm thick sections were prepared. Each tooth section was scanned and the length of dentin translucency was measured in GIMP 2.8 software. Results: A linear relationship was observed between dentin translucency and age in the regression analysis. Pearson's correlation analysis showed that there was positive correlation (r = 0.93, P = 0.001) between dentin translucency and age, and the difference between the chronologic age and real age is ± 4.88 years. Conclusion: Dentin translucency in the apical part of the tooth can be used for estimating the age of an individual. A method to digitally select and measure translucent root dentin length was used here. This software method is easy to use and less time-consuming. The measurements obtained using this method are more precise and thus help in more accurate age estimation. Considering these benefits, this study recommends the use of digital method to assess translucency for forensic purpose.